бўлажак физика ўқитувчиларининг Компетенцияларини шакллантиришда интерфаол таълим - Карлыбаева, Г.Е. (SCIENCE and SOCIETY, 2020)
The article deals with some issues on activating the process of teaching pre-service physics teachers, developing quality of lessons and using interactive methods in the future working process.
Keywords: continuous education; pre-service physics teacher; inter active teaching effectiveness of the lesson; methodical preparation; competency